2022
DOI: 10.1186/s43088-022-00277-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of ethno-phytomedicine knowledge in healthcare of COVID-19: advances in traditional phytomedicine perspective

Abstract: Background Since the outbreak of the COVID-19 virus, ethnomedicinal plants have been used in diverse geographical locations for their purported prophylactic and pharmacological effects. Medicinal plants have been relied on by people around the globe for centuries, as 80% of the world’s population rely on herbal medicines for some aspect of their primary health care needs, according to the World Health Organization. Main body This review portrays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…K. hybrida [120] Ethanol extract of the whole plant kalantubolide A (38) kalantubolide B (39) K. delagoensis [32] Flavonoids have been identified in aqueous, hydroalcoholic, and alcoholic extracts from the leaves of K. blossfeldiana, K. crenata; K. daigremontiana, K. delagoensis, K. fedtschenkoi, K. laciniata, K. marmorata, K. mortagei, and K. pinnata (compounds 40-78, Table 5 and Figure 4). The most common flavonoids/glycosylated flavonoids described from these species are derivatives of quercetin (40), patuletin (69)(70)(71), eupafolin (64), and kaempferol (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Aerial parts; methanol extract from the stemsStems eupafolin (6-methoxyluteolin) (64) K. ceratophylla [17,126] Aerial parts eupafolin 4 -O-rhamnoside (65) K. ceratophylla [126] Ethanol extract of the wholeWhole plant 4 -methoxyherbacetin (66) K. delagoensis [32] Stems and leaves; Leaves K. pinnata [129] Ethanol leaf extractLeaves luteolin (77) K. ceratophylla; K. pinnata [121,126] Ethanol leaf extractLeaves luteolin 7-O-β-D-glucoside (78) K. pinnata [121] Recently, a comprehensive approach encompassing metabolomics and machine learning techniques was implemented [134] to investigate K. daigremontiana, K. × houghtonii, and K. delagoensis plant tissue cultures.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…K. hybrida [120] Ethanol extract of the whole plant kalantubolide A (38) kalantubolide B (39) K. delagoensis [32] Flavonoids have been identified in aqueous, hydroalcoholic, and alcoholic extracts from the leaves of K. blossfeldiana, K. crenata; K. daigremontiana, K. delagoensis, K. fedtschenkoi, K. laciniata, K. marmorata, K. mortagei, and K. pinnata (compounds 40-78, Table 5 and Figure 4). The most common flavonoids/glycosylated flavonoids described from these species are derivatives of quercetin (40), patuletin (69)(70)(71), eupafolin (64), and kaempferol (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Aerial parts; methanol extract from the stemsStems eupafolin (6-methoxyluteolin) (64) K. ceratophylla [17,126] Aerial parts eupafolin 4 -O-rhamnoside (65) K. ceratophylla [126] Ethanol extract of the wholeWhole plant 4 -methoxyherbacetin (66) K. delagoensis [32] Stems and leaves; Leaves K. pinnata [129] Ethanol leaf extractLeaves luteolin (77) K. ceratophylla; K. pinnata [121,126] Ethanol leaf extractLeaves luteolin 7-O-β-D-glucoside (78) K. pinnata [121] Recently, a comprehensive approach encompassing metabolomics and machine learning techniques was implemented [134] to investigate K. daigremontiana, K. × houghtonii, and K. delagoensis plant tissue cultures.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The emergence of COVID-19, acknowledged as a 21st-century pandemic by the World Health Organization due to the zoonotic virus SARS-CoV-2 in late 2019, led to a global catastrophe with devastating repercussions. This virus triggers a spectrum of symptoms categorized by the WHO into common, less common and serious manifestations [1] .…”
Section: Introductionmentioning
confidence: 99%
“…showed that at least 80% of individuals in Africa rely mainly on the use of medicinal plants for healthcare delivery[53][54][55]. With the knowledge of the TMPs in medicinal plants,mode of preparation, and administration of the herbal mixture, successful treatment of some chronic ailments has been established.…”
mentioning
confidence: 99%